Threats of ecological-geomorphological safety and their mapping (for example territory Central Kazakhstan) (Journal of Geography and Environmental Management, 2016)
The basis of a cause hazards are the contradictions that arise from the interaction of internal and external events and factors that change over time its content and direction development. Environmental problems arising as a result of the manifestation of these risks, to varying degrees, affect morfolitogenic basis and related to them, exodynamic processes. Their solution involves the study of all components of the environment, and their aggregation on a certain basis. This is the basis of ecological and geomorphological environment, where differentiation is due to anthropogenic- modified morfolitogenical basis of the study area.
Keywords: ecological-eomorphological security